ANALISIS BUTIR SOAL UJIAN AKHIR SEMESTER MATA KULIAH MICRO TEACHING SEKOLAH TINGGI AGAMA ISLAM ALI BIN ABI THALIB SURABAYA TAHUN PELAJARAN 2020-2021 - Fauzi, Achmad (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2022)
This study aims to obtain information on the quality of the items for the Final Semester Examination of the Ali Bin Abi Thalib Islamic High School Surabaya for the 2020/2021 academic year. This research is a type of quantitative descriptive research. Final Examination Questions Semester microteaching course Ali Bin Abi Thalib Islamic High School Surabaya consists of 10 essay questions. The analysis of the end of semester exam questions is on the review of validity, reliability, discriminatory power, level of difficulty. The subjects of this study were students participating in the micro teaching lecture at STAI Ali Bin Abi Talib. The data collection technique in this statement uses the documentation method. Observational data analysis using the excel application program. The results of the research items for the Final Semester Examination of the Ali Bin Abi Thalib Islamic High School Surabaya subject have a validity level of 90% valid, the reliability is 0.792 including in the high reliability category, the discriminatory power is 60% in the medium and good criteria, and the level of Difficulty is classified as easy which ranges from 0.7 to 0.85.